Clinical insights and therapeutic strategies in Kindler syndrome: a comprehensive review - Ares, Mariana G. A.; Inclán, Valeria B. (International Journal of Research in Dermatology, 2024)
Kindler syndrome is a rare autosomal recessive genodermatosis characterized by acral blistering in infancy, photosensitivity, progressive poikiloderma, and skin atrophy. This review aims to provide an in-depth analysis of the clinical manifestations, molecular pathogenesis, diagnostic criteria, and therapeutic approaches for Kindler syndrome. We discuss the role of FERMT1 mutations in the disruption of keratinocyte adhesion and migration, contributing to the phenotypic features of the disease. Additionally, we examine the multidisciplinary management strategies encompassing dermatologic, ophthalmologic, and gastrointestinal care, emphasizing the importance of early diagnosis and personalized treatment plans. Emerging therapies and ongoing research into gene therapy and targeted molecular treatments are also explored. This comprehensive review seeks to enhance the understanding of Kindler syndrome among clinicians and researchers, fostering improved patient outcomes through informed clinical practice and innovative therapeutic developments.